2018
DOI: 10.3389/fpsyg.2018.00801
|View full text |Cite
|
Sign up to set email alerts
|

Are Adolescents Engaged in the Problematic Use of Social Networking Sites More Involved in Peer Aggression and Victimization?

Abstract: The problematic use of social networking sites is becoming a major public health concern. Previous research has found that adolescents who engage in a problematic use of social networking sites are likely to show maladjustment problems. However, little is known about its links with peer aggression and victimization. The main goal of this study was to analyze the relationship between problematic use of online social networking sites, peer aggression –overt vs. relational and reactive vs. instrumental–, and peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 87 publications
10
71
0
5
Order By: Relevance
“…These results are consistent with the two-factor structure of the CBVEQ-G scale by Antoniadou et al (2016), who also classify their items as indirect aggressions and direct aggressions. These results are also congruent with previous literature on traditional bullying that points to the existence of these two dimensions of peer violence, referred to as direct or manifested aggressions and indirect or relational aggressions (Martínez-Ferrer et al 2018;Mynard and Joseph 2000;Little et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with the two-factor structure of the CBVEQ-G scale by Antoniadou et al (2016), who also classify their items as indirect aggressions and direct aggressions. These results are also congruent with previous literature on traditional bullying that points to the existence of these two dimensions of peer violence, referred to as direct or manifested aggressions and indirect or relational aggressions (Martínez-Ferrer et al 2018;Mynard and Joseph 2000;Little et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…School victimization: The Spanish version of the School Victimization Scale [51], adapted by Martínez-Ferrer, Moreno, and Musitu [4], was used. This scale consists of 20 items that measure, on a response range of 1 (never) to 4 (always), the frequency with which students have been subjected to violent behavior in the last year.…”
Section: Instrumentsmentioning
confidence: 99%
“…School victimization is defined as a type of peer abuse in which students are subjected to violent verbal, physical, and psychological behavior by one or more peers [1,2]. This problem has serious consequences for the development and psychosocial adjustment of students [3][4][5]. As regards gender, data suggest that, in the case of school victimization, boys are victimized by their partners overtly and girls relationally [6,7], although some studies have not reported such differences [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For adolescents, smartphones-mobile phones with Internet access-virtual social media, and instant messaging, are part of their daily lives and they provide them with a connected environment for development and socialization (Livingstone et al 2011;Wachs et al 2016). However, this incursion of ICT in the day-to-day lives of adolescents also has many negative effects, such as, for example, Internet addiction and behaviors that are associated with cyberbullying (Aricak and Ozbay 2016;Martínez-Ferrer et al 2018). Recent studies have revealed the alarming increase in cyberbullying in all developed countries, which has raised great concern in social and educational spheres (De Santisteban and Gámez-Guadix 2017; Garaigordobil 2017; Kowalski et al 2014;Ortega-Barón et al 2016).…”
Section: Introductionmentioning
confidence: 99%